Analysis of the structural and electronic properties of 1-(5-Hydroxymethyl-4–[5–(5-oxo-5-piperidin-1-yl-penta-1,3dienyl)-benzo[1,3]dioxol-2-yl]-tetrahydro-furan-2-yl)-5-methyl-1H-pyrimidine-2,4dione molecule - Essa, Ali Hashem; Jalbout, Abraham F. (Eclética Química, 2008)
The structural and electronic properties of 1-(5-Hydroxymethyl - 4 –[ 5 – (5-oxo-5-piperidin- 1 -yl-penta- 1,3 -dienyl)-benzo [1,3] dioxol- 2 -yl]- tetrahydro -furan-2 -yl)-5-methy l-1Hpyrimidine-2,4dione (AHE) molecule have been investigated theoretically by performing density functional theory (DFT), and semi empirical molecular orbital calculations. The geometry of the molecule is optimized at the level of Austin Model 1 (AM1), and the electronic properties and relative energies of the molecules have been calculated by density functional theory in the ground state. The resultant dipole moment of the AHE molecule is about 2.6 and 2.3 Debyes by AM1 and DFT methods respectively, This property of AHE makes it an active molecule with its environment, that is AHE molecule may interacts with its environment strongly in solution.